First world petro-politics : the political ecology and governance of Alberta - Adkin, Laurie Elizabeth, 1958- (University of Toronto Press, 2016)
"First World Petro-Politics examines the vital yet understudied case of a first world petro-state facing related social, ecological, and economic crises in the context of recent critical work on fossil capitalism."-- Provided by publisher
Keywords: Petroleum industry and trade -- Political aspects -- Alberta.; Petroleum industry and trade -- Government policy -- Alberta.; Petroleum industry and trade -- Social aspects -- Alberta.; Petroleum industry and trade -- Environmental aspects -- Alberta.; Alberta -- Politics and government.; Alberta -- Economic policy.; Pétrole -- Industrie et commerce -- Aspect politique -- Alberta.; Pétrole -- Industrie et commerce -- Politique gouvernementale -- Alberta.; Pétrole -- Industrie et commerce -- Aspect social -- Alberta.; Pétrole -- Industrie et commerce -- Aspect de l'environnement -- Alberta.; Alberta -- Politique et gouvernement.; Alberta -- Politique économique.; BUSINESS & ECONOMICS -- Industries -- General.; NATURE -- Environmental Conservation & Protection.; Economic policy; Petroleum industry and trade -- Environmental aspects; Petroleum industry and trade -- Government policy; Petroleum industry and trade -- Political aspects; Petroleum industry and trade -- Social aspects; Politics and government; Alberta